2013
DOI: 10.1139/cjpp-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cardiomyocyte apoptosis in myocardial injury of hereditary epileptic rats

Abstract: Many clinical cases have been reported where epilepsy profoundly influenced the pathophysiological function of the heart; however, the underlying mechanisms were not elucidated. We use the tremor (TRM) rat as an animal model of epilepsy to investigate the potential mechanisms of myocardial injury. Cardiac functions were assessed by arrhythmia score, heart rate, heart:body mass ratio, and hemodynamic parameters including left ventricular systolic pressure (LVSP), left ventricular end-diastolic pressure (LVEDP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Our results indicated that the protein expression of CaSR was upregulated in TRM rat hearts, and this change strongly suggested that CaSR might be involved in epilepsy-induced cardiac injury. We previously found remarkable cardiac dysfunction and cardiomyocyte apoptosis in TRM rat hearts [14]. In this study, we also observed cardiac collagen deposits in TRM rat hearts.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our results indicated that the protein expression of CaSR was upregulated in TRM rat hearts, and this change strongly suggested that CaSR might be involved in epilepsy-induced cardiac injury. We previously found remarkable cardiac dysfunction and cardiomyocyte apoptosis in TRM rat hearts [14]. In this study, we also observed cardiac collagen deposits in TRM rat hearts.…”
Section: Discussionsupporting
confidence: 69%
“…Total proteins of the left ventricle myocardium were prepared and quantified using the BCA protein assay reagent, and the expression of specific proteins was analyzed through Western blot analysis as previously described by Chen et al [14]. Primary antibodies were as follows: CaSR (1:2,000), caspase-3 (1:200), Bcl-2 (1:200), Bax (1:200), ERK1/2 (1:200), JNK (1:200), p38 (1:200), TGF-β 1 (1:400), CTGF (1:2,000), collagen I (1:2,000), collagen III (1:2,000), and GAPDH (1:5,000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cardiomyocyte apoptosis may be associated with activation of the mitogenactivated protein kinase pathway and mitochondria-initiated intrinsic pathway. 30 While many studies have focused on noting changes in electrocardiogram measurements, blood pressure, and myocar- dial histopathology, the underlying molecular mechanisms and involved biological pathways associated with cardiac injury in epilepsy remain elusive. In this study, we used iTRAQ-based proteomics to examine rat myocardial tissue and to explore molecular proteomic differences to reveal physiological/ pathological mechanisms leading to cardiac injury after recurrent seizures.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The downregulation of ASK1 expression may reduce apoptosis and the myocardial infarct size in a rat model of ischemia/reperfusion [ 35 ]. Moreover, it has been reported that cardiomyocyte apoptosis is involved in the myocardial injury of tremor rats by reducing Bcl-2 and p-ERK1/2, upregulating Bax, p-JNK, and p-p38, and activating caspase-3 [ 36 ]. In this study, we determined that miR-320 regulates the expression of Bax, Bcl-2, cleaved caspase-3, cleaved caspase-9, p-ASK1, p-JNK and p-p38 in cardiomyocytes after H/R injury by targeting AKIP1.…”
Section: Discussionmentioning
confidence: 99%